Eksplorasi Teknik Twisting pada Material Bonggol Jagung - Radhika BIzanthiyum Hizrafi Risteruw; Andry Masri (Jurnal Desain Indonesia., 2023)
This research is an exploration of the form of corn cobs using the twisting technique. This technique involves applying pressure to the two ends of the corn cob module in opposite directions. The research also includes experiments to multiply the twisted modules using a mold. This study is a development of previous research that utilized bending on corn cob materials by first making the corn cobs soft. The aim of this research is to discover new forms, as previous research tends to utilize cylindrical modules and geometric shapes resulting from lamination techniques and bending techniques. At the end of the research, a composition of corn cob modules using the twisting technique is created, aiming to find the appropriate composition to serve as the basis for product design. This research is conducted through a direct experimental approach on corn cob materials at the corn cob processing industry in PT Matahati Kreasi Nusantara, Bandung.